Bullying Prevention Assistance For Elementary School Students In Simogirang Village Sidoarjo Regency - Aurellia, Sarah Putri (LPPM Universitas Yudharta Pasuruan, 2023)
Education in Indonesia focuses on making students into human beings who are noble, knowledgeable, creative, independent, and become responsible citizens for their behavior. But even though education or school has good goals, it cannot be denied that the phenomenon of bullying is still rampant among Indonesian students. This service activity was carried out at SDN Simogirang 1 and 2 using the Participation Action Research method. Researchers use a phenomenological design to reveal the facts behind the phenomenon of bullying that occurs in elementary school children. It is important to educate elementary school students about bullying, because this is an effective first step in preventing bullying. In an effort to prevent the dangerous phenomenon of bullying, socialization in elementary schools has proven to be an effective and important approach